THE ROLE OF KNOWLEDGE MANAGEMENT PROCESSES IN ACHIEVING AND ENHANCING SUSTAINABLE COMPETITIVE ADVANTAGE (A FIELD STUDY ON PRIVATE UNIVERSITIES IN ALMUTHANNA GOVERNORATE) (World Bulletin of Management and Law, 2023)
This study aims to identify the role of knowledge management processes in achieving, enhancing and sustaining the competitive advantage in private universities in Al-Muthanna Governorate from the point of view of a sample of teachers and employees at Imam Al-Sadiq University Al-Muthanna Branch, and Sawa private University, where (120) questionnaires were distributed The study model was developed to take into account the relationship between the independent variables represented in knowledge management processes (acquisition, generation, application, distribution) and the dependent variable represented in the sustainable competitive advantage, which includes its various dimension